Specific, sensitive, and rapid diagnosis of active Toxoplasmosis by a Loop-Mediated Isothermal Amplification method using blood samples from patients - Lau, Y.L.; Meganathan, P.; Sonaimuthu, P.; Thiruvengadam, G.; Nissapatorn, V.; Chen, Y. (2010)
Loop-mediated isothermal amplification (LAMP), a rapid nucleic acid amplification method, was developed for the clinical diagnosis of toxoplasmosis. Three LAMP assays based on the SAG1, SAG2, and B1 genes of Toxoplasma gondii were developed. The sensitivities and specificities of the LAMP assays were evaluated by comparison with the results of conventional nested PCR. The LAMP assays were highly sensitive and had a detection limit of 0.1 tachyzoite, and no cross-reactivity with the DNA of other parasites was observed. Blood was collected from 105 individuals to test the LAMP assays: 40 patients with active toxoplasmosis, 40 negative controls, and 25 patients with other parasitic infections. The SAG2-based LAMP (SAG2-LAMP) had a greater sensitivity (87.5) than the SAG1-LAMP (80), B1-LAMP (80), and nested PCR (62.5). All the LAMP assays and nested PCR were 100 specific. This is the first report of a study which applied the LAMP method to diagnose toxoplasmosis from human blood samples. Due to its simplicity, sensitivity, and specificity, LAMP is suggested as an appropriate method for routine diagnosis of active toxoplasmosis in humans.